Exosome-mediated communication between gastric cancer cells and macrophages: implications for tumor microenvironment - Qiu, Yue; Lu, Guimei; Li, Na; Hu, Yanyan; Tan, Hao; Jiang, Chengyao (Frontiers in Immunology, 2024)
Gastric cancer (GC) is a malignant neoplasm originating from the epithelial cells of the gastric mucosa. The pathogenesis of GC is intricately linked to the tumor microenvironment within which the cancer cells reside. Tumor-associated macrophages (TAMs) primarily differentiate from peripheral blood monocytes and can be broadly categorized into M1 and M2 subtypes. M2-type TAMs have been shown to promote tumor growth, tissue remodeling, and angiogenesis. Furthermore, they can actively suppress acquired immunity, leading to a poorer prognosis and reduced tolerance to chemotherapy. Exosomes, which contain a myriad of biologically active molecules including lipids, proteins, mRNA, and noncoding RNAs, have emerged as key mediators of communication between tumor cells and TAMs. The exchange of these molecules via exosomes can markedly influence the tumor microenvironment and consequently impact tumor progression. Recent studies have elucidated a correlation between TAMs and various clinicopathological parameters of GC, such as tumor size, differentiation, infiltration depth, lymph node metastasis, and TNM staging, highlighting the pivotal role of TAMs in GC development and metastasis. In this review, we aim to comprehensively examine the bidirectional communication between GC cells and TAMs, the implications of alterations in the tumor microenvironment on immune escape, invasion, and metastasis in GC, targeted therapeutic approaches for GC, and the efficacy of potential GC drug resistance strategies.